2021
DOI: 10.20944/preprints202104.0357.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Nitrogen Ion Implantation on the Cavitation Erosion Resistance and Cobalt-Based Solid Solution Phase Transformations of HIPed Stellite 6

Abstract: From the wide range of engineering materials traditional Stellite 6 alloy exhibits excellent cavitation erosion (CE) resistance. In this work, the effect of nitrogen ion implantation of HIPed Stellite 6 on the improvement of CE resistance and both cobalt-rich matrix phase transformation due to nitrogen implantation and CE were stated. The CE resistance of stellites ion-implanted by 120 keV N+ ions two fluences: 5x1016 cm-2 and 1x1017 cm-2 were comparatively analysed with the unimplanted stellite and AISI 304 s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Implantation of transition metals like Cr or Ni could be used for enhancing the corrosion resistance of metals and alloys [11][12][13] as well as for improvement of their tribological [14], fatigue [15] and erosive [16] properties. It was also shown that formation of intermetalic Laves phases in titanium and ZrNb alloy is possible via Cr + ion implantation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Implantation of transition metals like Cr or Ni could be used for enhancing the corrosion resistance of metals and alloys [11][12][13] as well as for improvement of their tribological [14], fatigue [15] and erosive [16] properties. It was also shown that formation of intermetalic Laves phases in titanium and ZrNb alloy is possible via Cr + ion implantation [17,18].…”
Section: Introductionmentioning
confidence: 99%